The Religious Behavior of Rural Communities is the Challenge in Handling the Covid-19 Pandemic in Semarang Regency - Subqi, Imam; Maftuh, Hasan; Alwi, M. Mustoliq (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The Covid-19 pandemic has impacted all sectors of life, such as changing religious behavior, the number of layoffs, online learning, restrictions on transportation modes. The purpose of this study was to determine the policies for handling the covid-19 outbreak in Semarang Regency and the maturity of community diversity in dealing with policies for handling the COVID-19 pandemic with a qualitative research approach. The results of this study indicate that (1) the policy for handling the covid-19 outbreak in Semarang Regency follows the central government policy, namely large-scale social restrictions,(2) the maturity of the community's religion in dealing with policies for handling the COVID-19 pandemic, including (a) good differentiation, religious behavior in responding to health protocol regulations by wearing masks, washing hands, or using hand sanitizers, keeping a distance in worship away from crowds. (b) dynamic religious life motivation, continuing to pray and implementing health protocols can reduce and even reduce Covid-19 sufferers, (c) consistent and productive implementation of religious teachings, continue to worship with health protocols such as tahlilan, yasinan, ma'tsurat, prayers congregations, holiday gatherings, birthdays of the apostles and other activities. (d) a comprehensive view of life, the community has a moderate perspective with mutual respect and appreciation. (e) an integral view of life, by reminding each other and quickly finding solutions when there are problems, (f) the spirit of seeking and serving God, the community is increasingly aware of the importance of maintaining health, cleanliness, and praying for the common good.